Recent advances and perspectives in ruthenium-catalyzed cyanation reactions - Aneeja, Thaipparambil; Afsina, Cheriya Mukkolakkal Abdulla; Saranya, Padinjare Veetil; Anilkumar, Gopinathan (Beilstein Journal of Organic Chemistry, 2022)
The cyanation reaction has achieved rapid progress in recent times. The ability to exhibit multiple oxidation states increased the demand of ruthenium in the field of catalysis. These cyanation reactions have wide application in pharmacological and biological fields. This review gives an overview of the ruthenium-catalyzed cyanation reactions covering literature up to 2021.
Keywords: cyanation; nitriles; photocatalyst; ruthenium; tertiary amines